The Dangers of Gadgets on Teenagers' Mind Focus:Thematic and Analytical Study on QS. Al-Baqarah Verse 171 - Fani Firda Yuniarti (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the dangers of gadgets on the focus of teenagers' minds, a thematic and analytical study on QS al-Baqoroh ayait 171. Remembering that the intellect that Allah swt. Granted to humans, this is one of the forms of human perfection compared to animals. The intellect that Allah gave to humans is what we use to think when doing everything. With reason and rational thinking, we can gain various kinds of new knowledge. So, there are various kinds of innovations and new creations from scientists that are useful in helping humans with daily activities. One form of the development and progress of science and technology (IPTEK) is gadgets. This object is a form of the development of science and technology, with a function to facilitate all kinds of human work in this digital era. However, these objects also have a negative impact and cause users to be addicted. A very visible impact of using gadgets is the loss of focus in every human being. The loss of focus can occur due to the disruption of the use of the sense of hearing; this sense is not functioning properly. This research discusses the impact of gadgets on the focus of teenagers' minds. Thematically, this research discusses the events that occur in teenage children caused by gadget addiction and then examines them with thematic analytical methods based on the perspective of Tafsir on QS. Al-Baqarah [2]: 171. To find out the content contained in the verse, researchers conducted research using literature studies. Through related literature and using one of the works of Fakhr al-Di? al-R?z?, The author quotes Piet Hizbullah Khaidir in explaining the focus of the mind that is lost due to reluctance to hear. This study found that hearing loss occurs due to reluctance to hear, which is the cause of loss of concentration and is one of the consequences of gadget addiction.